AREAS OF APPLICATION OF TEMPERATURE BASED DDU MODELS FOR PREVENTION OF DIROFILARIASIS - E. Y. Krivorotova; S. A. Nagorny (Российский паразитологический журнал, 2016)
Objective of research: To study the possibility of using temperature-based models for prevention of dirofilariasis. Materials and methods. For mathematical modeling of dirofilariasis we use the HDUstemperature model based on the impact of the average daily temperature on the rate of development of Dirofilaria larvae in mosquitoes.The amount of 130 DDU (Dirofilaria development units) accumulated in the period no more than 30 days at average daily temperature more than 14◦C is required for the development of Dirofilaria up to the infective stage.Daily data on average air temperature in Rostov-on-Don (1996 — 2012), Veliky Novgorod (2008 — 2012), Anapa (2008 -2012) and Astrakhan (2008 -2012) were used for the calculation.Results and discussion. The results of temperature simulation revealed that the DDU model is a low-priority forecasting model for canine dirofilariasis (Pearson’s correlation coefficient minus 0.45). The model considers only the average daily temperature and does not consider other factors affecting the incidence rates.The epidemic season of dirofilariasis in Rostov-on-Don in 1999 — 2012 differed depending on average daily temperatures. Therefore, the earliest date of the transmission of dirofilariasis in that period fell on the 12th of May, 2012; the latest date — on 29th of June, 2001. The optimal time for prevention of canine dirofilariasis has been defined (in Rostov-on-Don, Anapa and Astrakhan microfilaricides should be given to dogs from May 15 to November 15; in Veliky Novgorod — from June 15 to August 31).Thus, DDU-models (Dirofilaria Development Units) can be used to set time limits for epidemiological season of dirofilariasis and preventive treatment of dogs against dirofilaria.